PENGELOLAAN HOMESTAY SESUAI PROTOCOL COVID-19 DI DESA WARGASARA, KABUPATEN SERANG, PROVINSI BANTEN - Bangga Prameswara (Pusat Perencanaan dan Pengembangan Kepariwisataan, 2022)
Corona Virus Disease 19 or also known as Covid-19 is currently having a huge impact on the Indonesian tourism industry. Most of the tourism business players in Indonesia were forced to stop their business operations. During the quarter the first of 2020, international tourist arrivals fell by 60-80%. This shows that the current state of tourism it's in bad shape. To anticipate the spread of Covid-19, the Indonesian government has made a standard health protocols that will be applied in the tourism sectors, such as hotels, tourist destinations, restaurants, and homestays existing in Indonesia. Especially in the homestay sector, the results of observations made show that not all homestays apply the covid-19 protocol for their businesses, but there are also districts that already have certificates